<En>coding performance: from analogue to digital. Issue 2 (2nd July 2016) - Allan, Hannah Elizabeth
ABSTRACT: This paper explores the connection between contemporary Live Coding practice in relation to the earlier forms of text-based performance and documentation used within the Fluxus movement. Analysing these works has allowed for a connection to be made, and an argument put forward that live coding in performance is not limited to digital work alone, but rather has a lineage linked through language and the symbiotic relationship created between performer and text. During the Fluxus movement of the early 1960s, a form of performance art emerged through the text score that acted as the ultimate reduction of the scripted form. Alongside static scores, artists began to use a process of live typing and recording to both document performance and alter their own environments. This aligns with the performative work of Live Coding, which has its own specific algorithmic syntax, creating a looping response between performer and text.